Academic Productivity, Knowledge, and Education in Plastic Surgery: The Benefit of the Clinical Research Fellow. Issue 4 (October 2017) - Carney, Martin J.; Weissler, Jason M.; Koltz, Peter F.; Fischer, John P.; Wu, Liza C.; Serletti, Joseph M.
Abstract : Background: Academic research productivity is limited by strenuous resident and faculty schedules but nevertheless is imperative to the growth and success of our discipline. The authors report institutional experience with their clinical research fellowship model, providing two positions per year. Methods: A critical analysis of research productivity was performed for all trainees, faculty, and research fellows from 2000 to 2015. Academic productivity was determined by the number of peer-reviewed publications, podium presentations, and h-index. Academic fate of previous research fellows was also noted. During the 16-year timeframe, 484 articles were published in print. Notably, 92 articles were published from 2000 to 2007 and 392 articles were published from 2008 to 2015 ( p = 0.0066), demonstrating linear growth after instituting the research fellowship. In addition, 33 articles were published from 2002 to 2004 before leadership change, 47 from 2005 to 2007 after leadership change but before fellowship, and 58 from 2008 to 2010 in the first few years of the fellowship ( p = 0.0204). Results: Overall, 39.9 percent of publications appeared in Plastic and Reconstructive Surgery, with a total of 77 different peer-reviewed journal inclusions. American Association of Plastic Surgeons, American Society of Plastic Surgeons, and Northeastern Society of Plastic Surgeons podium presentations totaled 143 between 2005 and 2015. Of the eight previous fellows who applied into integrated and independent programs, 100 percent have matched. Conclusion: Incorporation of a formalized research fellowship into a plastic surgery program can drastically increase clinical research contribution in a reproducible fashion.